2017
DOI: 10.12973/eurasia.2017.01241a
|View full text |Cite
|
Sign up to set email alerts
|

Graduate Employability: The Perspective of Social Network Learning

Abstract: This study provides a conceptual framework for understanding how the graduate acquire employability through the social network in the Chinese context, using insights from the social network theory. This paper builds a conceptual model of the relationship among social network, social network learning and the graduate employability, and uses structural equation analysis method to conduct an empirical test on the theoretical hypothesis, based on a sample of 1468 fresh graduates of business discipline from the loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Graduates are viewed as "complete" products in terms of their qualifications, but this theory-based knowledge has to be supported by the employee's willingness to learn on-the-job and respond to the demands and challenges of the organisation pertaining to aspects such as to working hours, salary, and benefits. As reiterated by Zakaria, Yusoff, Ibrahim and Tibok (2020), there is a real need to establish cohesive cooperation and collaboration frameworks between industry and institutions of higher learning as such networks would certainly help provide job exposure and working life insights while at the same time build their work-related social network (Yong, 2017), promote employment opportunities and improve undergraduates' opportunities of joining these organisations at a later stage. In this respect, universities have a critical role in ensuring that these elements of graduate capital-building are integrated within their curriculum and what is taught in the lecture halls fit into the needs and expectations of industry as the end-receiver of the human capital products.…”
Section: Workplace Environment Readiness and Resiliencementioning
confidence: 99%
“…Graduates are viewed as "complete" products in terms of their qualifications, but this theory-based knowledge has to be supported by the employee's willingness to learn on-the-job and respond to the demands and challenges of the organisation pertaining to aspects such as to working hours, salary, and benefits. As reiterated by Zakaria, Yusoff, Ibrahim and Tibok (2020), there is a real need to establish cohesive cooperation and collaboration frameworks between industry and institutions of higher learning as such networks would certainly help provide job exposure and working life insights while at the same time build their work-related social network (Yong, 2017), promote employment opportunities and improve undergraduates' opportunities of joining these organisations at a later stage. In this respect, universities have a critical role in ensuring that these elements of graduate capital-building are integrated within their curriculum and what is taught in the lecture halls fit into the needs and expectations of industry as the end-receiver of the human capital products.…”
Section: Workplace Environment Readiness and Resiliencementioning
confidence: 99%
“…Graduate employability can be defined as the compilation of a series of soft and hard skills and abilities that a graduate can obtain to achieve and meet a desirable job requirement and succeed in his/her career [8]- [12]. Based on the related works that primarily started from the 1990s, we can separate this series of skills into two categories :…”
Section: Graduate Employabilitymentioning
confidence: 99%
“…Their study found no difference between males and females in gaining employability skills. In the Chinese context, Chen 15 used the following dimensions of employability skills to investigate the relationships between social networks, social network learning, and graduate employability: professional self-identity, learning ability, teamwork skills, career planning ability, and social adaptability. In Kuwait, Al-Mutairi et al 16 explored the importance of four primary groups of employability skills to the employer: soft skills, graduates' knowledge; personal abilities; and teamworking.…”
Section: Employability Skills Emotional Competencies and Employmentmentioning
confidence: 99%